Robotic navigation system based on BLE beacons and QR code - Siak, Hui Mun (Nanyang Technological University, 2021)
Localisation and navigation have become a very important aspect of the modern lifestyle. In an outdoor setting, satellites are used to determine the location of a user or device. Indoor localisation, however, continues to pose a challenge. Many methods have emerged, each with its strengths and weaknesses. The Robotic Navigation System is a cost-efficient system that uses Bluetooth Low Energy (BLE) beacons and Quick Response (QR) codes as indicators of destinations. The robot uses the Received Signal Strength Indicator (RSSI) of Bluetooth, together with an algorithm to determine a route towards a destination without the need for prior mapping of location